Enhancement of Electrospinning Machine Process Using IoT - Tan, Wei Hong; Koh, Ching Theng (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In conventional electrospinning monitoring system, we might waste a big chunk of our own time if traditional way is used for monitoring the temperature and humidity in the machine. Besides, due to pandemic Covid-19 we need to practice social distancing, and the traditional monitoring system does not allow operator to monitoring on the situations and condition data from far end. This data plays an important role to allow the operator to monitoring the situation and condition inside the electrospinning machine and optimize the quality of fiber produced. In this project, the system that needed to develop is about the IoT monitoring system for electrospinning process using the Raspberry Pi 4 Model B microcontroller as the main board. There are two parameters that will be monitoring, which are air temperature and air humidity. Temperature sensor, humidity sensor and camera module was connected to the Raspberry Pi 4 Model B microcontroller. The Python programming language is the official operating system for Raspberry Pi, Raspbian, was used to install the Node-RED and camera interface for monitoring. The data will then send to a website for the user to monitor and send to a cloud database for storage. A code in JavaScript language will write to give the corresponding instruction to ensure the web application to give warning when the data collected is exceed the threshold. The system that has developed in this project is able to reduce the working time for operator in front of the electrospinning machine to monitor the process. Besides, the quality of fibers is able to be optimized by the system in this project.